PENERAPAN MODEL INQUIRY LEARNING UNTUK MENINGKATKAN HIGHER ORDER THINKING SKILLS MATERI MOMENTUM DAN IMPULS - Meutia, Inarsih; Sitompul, Stepanus Sahala; Mahmuda, Diah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is purposed to find out the effectiveness of the implementation of Inquiry learning in improving the Higher Order Thinking Skills (HOTS) of the students in momentum and impulse. Pre-Experimental design with one group pre-test and post-test was used in this research. The population is all the IPA students at the 10th grade of SMAN 1 Sukadana. Using intact group, the sample of this research was X IPA 1 that have 32 studentes. This research instrument used HOTS test that have 5 essay questions. The average of the students  HOTS test result before the implementation of inquiry learning was 4.09 in enough category, whereas the students HOTS test result after the implementation of inquiry learning was at 11.4 in the very good category. Wilcoxon nonparametric test was applied with significance at 5% which shows there is an enhancement after the implementation of inquiry learning. Inquiry learning model is effective to improve the students HOTS in the momentum and impulse subject in effect size score 4.4 in the high category according to Cohen. As the result inquiry model can be used as the alternative learning model to improve students? HOTS. Keyword: Higher Order Thinking Skills (HOTS), inquiry learning, momentum and     impulse